Study Of Wave Soldering Using Thermal-Fluid Structure Interaction Technique On Pin Through Hole In Printed Circuit Board - Aziz, Mohd Sharizal Abdul (2015)

(untitled)
Wave soldering is one of the most familiar and well-established processes in the electronics assembly industry, which is used to assemble the pin-through hole (PTH) component onto the printed circuit board (PCB). The solder joint defects such as cracks, void formation, and incomplete filling of the PCB hole may weaken the PTH solder joint. In the present research, the PTH vertical fill was carried out experimentally by using a newly developed adjustable fountain wave soldering machine (0° conveyor angle). A similar PCB and components were assembled by using a conventional wave soldering machine (6° conveyor angle). A non-destructive X-ray computed tomographyscanning machine was employed to inspect the vertical fill of each solder joint. On the other hand, the wave soldering process considering thermal-FSI phenomenon was the focus on this research. The thermal-FSI simulation was carried out by using finite volume (FLUENT) and finite element (ABAQUS) based software through the real time coupling technique using Mesh-based parallel Code Coupling Interface (MpCCI) software. It was found that the adjustable fountain wave soldering yielded higher vertical fill (~99.4%) than the conventional wave soldering machine (~90.8%). Apart from that, the simulations were broadening to the parametric studies on various process and design factors such as conveyor angle and PTH geometry (i.e. offset position, shape, diameter,offset angle). The influences of these parameters on the fluid flow distribution, structural displacement, pressure distribution, and stress have been highlighted. Moreover the optimization of PTH connector in the wave soldering process using response surface methodology (RSM) was handled to study the interactive relationship between independent variables to the responses. The optimum geometrical and process parameters for the PCB and PTH connector were characterized by 0.12 mm of PTH offset position, 0.17 mm of PTH diameter, 0o of offset angle and 473.15 K of molten solder temperature. Finally the case study on the effects of PCB configuration during wave soldering was investigated. Five PCB configurations were considered based on the position of the components. Results show that PCB component configurations significantly influence the PCB and yield unfavorable deformation and stress. The research findings are expected to be significant contributions in for the microelectronic industry